An Evolutionary Approach to the History of Barley (Hordeum vulgare) Cultivation in the Canary Islands. - Hagenblad, Jenny; Morales, Jacob (African Archaeological Review, 2020)
The Canary Islands are an archipelago that lies about 100 km west of North Africa. Barley (Hordeum vulgare) has been continuously cultivated since the colonization of the islands. To investigate the agricultural history of the islands, the DNA from multiple individuals of six extant landraces of barley was sequenced, and the resulting data were analyzed with ABC modeling. Estimates of separation times of barley populations on the different islands and the mainland were congruent with archaeological dating of the earliest settlements on the islands. The results of the genetic analyses were consistent with the continuous cultivation of barley on Lanzarote island since it was first colonized, but suggested cultivation was carried out at a smaller scale than on Gran Canaria and Tenerife. Contrary to archaeological evidence and early written historical sources, the genetic analyses suggest that barley was cultivated on a larger scale on Tenerife than on Gran Canaria. The genetic analysis of contemporary barley added support to the dating of the colonization of the islands and pointed to the need for more archaeological data concerning barley cultivation on Tenerife.